Acrylamide-induced oxidative stress and inflammatory response are alleviated by N-acetylcysteine in PC12 cells: Involvement of the crosstalk between Nrf2 and NF-κB pathways regulated by MAPKs - Pan, Xiaoqi; Wu, Xu; Yan, Dandan; Peng, Cheng; Rao, Chaolong; Yan, Hong (Toxicology letters, 2018)
•Oxidative stress and inflammatory response induced by acrylamide in PC12 cells were revealed.•A crosstalk between Nrf2 and NF-κB signaling pathways regulated by MAPKs existed in ACR-induced cell damage.•NAC could protect against oxidative damage and inflammatory response induced by ACR via regulating Nrf2 and NF-κB pathways. Acrylamide (ACR) is a classic neurotoxin in animals and humans. However, the mechanism underlying ACR neurotoxicity remains controversial, and effective prevention and treatment measures against this condition are scarce. This study focused on clarifying the crosstalk between the involved signaling pathways in ACR-induced oxidative stress and inflammatory response and investigating the protective effect of antioxidant N-acetylcysteine (NAC) against ACR in PC12 cells. Results revealed that ACR exposure led to oxidative stress characterized by significant increase in reactive oxygen species (ROS) and malondialdehyde (MDA) levels and glutathione (GSH) consumption. Inflammatory response was observed based on the dose-dependently increased levels of pro-inflammatory cytokines tumor necrosis factor-α (TNF-α) and interleukin 6 (IL-6). NAC attenuated ACR-induced enhancement of MDA and ROS levels and TNF-α generation. In addition, ACR activated nuclear transcription factor E2-related factor 2 (Nrf2) and nuclear factor-κB (NF-κB) signaling pathways. Knockdown of Nrf2 by siRNA significantly blocked the increased NF-κB p65 protein expression in ACR-treated PC12 cells. Down-regulation of NF-κB by specific inhibitor BAY11-7082 similarly reduced ACR-induced increase in Nrf2 protein expression. NAC treatment increased Nrf2 expression and suppressed NF-κB p65 expression to ameliorate oxidative stress and inflammatory response caused by ACR. Further results showed that mitogen-activated protein kinases (MAPKs) pathway was activated prior to the activation of Nrf2 and NF-κB pathways. Inhibition of MAPKs blocked Nrf2 and NF-κB pathways. Collectively, ACR activated Nrf2 and NF-κB pathways which were regulated by MAPKs. A crosstalk between Nrf2 and NF-κB pathways existed in ACR-induced cell damage. NAC protected against oxidative damage and inflammatory response induced by ACR by activating Nrf2 and inhibiting NF-κB pathways in PC12 cells.